Frontalis Sling Procedure Using Prolene Material in Severe Ptosis (Faridpur Medical College Journal, 2017)
Abnormally low position (drooping) of the upper eye lid is called ptosis. Common practices in correction of ptosis are different types of surgical procedures like, Fasanella-Servat procedure, Levator resection, Frontalis brow suspension (sling), Aponeurosis strengthening etc. In sling operation different types of materials are used, like, autogenus fascialata, cadaver fascilata, skin, sclera, collagen and artificial eg. Prolene, ethibond, silicone, supramid, mersilene mesh, goretex etc. The aim of study is to establish that use of prolene in sling operation gives better result. The study was carried out at BSMMU. A total thirty cases were selected for study. Technique of operation was Frontalis brow suspension (sling) procedure using prolene. The follow-up period was three months to six months. Final outcome of ptosis correction was good outcome in 24 (80%) patients out of 30. So prolene use in sling operation has excellent tensile strength, good handling properties, permanent result and better tolerance.Faridpur Med. Coll. J. Jan 2017;12(1): 31-33